2017
DOI: 10.1111/2041-210x.12759
|View full text |Cite
|
Sign up to set email alerts
|

Non‐destructive estimation of above‐ground surface and near‐surface biomass using 3D terrestrial remote sensing techniques

Abstract: Summary Quantitative measurements of above‐ground vegetation biomass are vital to a range of ecological and natural resource management applications. Remote‐sensing techniques, such as terrestrial laser scanning (TLS) and image‐based point clouds, are potentially revolutionary techniques for measuring vegetation biomass and deriving other related, structural metrics for these purposes. Surface vegetation biomass (up to 25 cm) in pasture, forest, and woodland environments is estimated from a 3D point cloud de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
75
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 20 publications
8
75
0
Order By: Relevance
“…Remote sensing images and aerial photogrammetry promptly obtain forest surface data over a large area. However, these two methods have a limitation because the accuracy of the terrestrial data under the tree crown is compromised [10][11][12][13]. 3D laser scanning technology can efficiently collect high precision 3D data of a forest's vertical structure.…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing images and aerial photogrammetry promptly obtain forest surface data over a large area. However, these two methods have a limitation because the accuracy of the terrestrial data under the tree crown is compromised [10][11][12][13]. 3D laser scanning technology can efficiently collect high precision 3D data of a forest's vertical structure.…”
Section: Introductionmentioning
confidence: 99%
“…Surface fuel load was calculated for both visually assessed and point cloud data by inputting estimates of surface litter depth (height) and percent cover obtained via the two methods into the following Equation (2) as per Wallace et al [40]:Fuel load =1.46 × height × cover(π × 102)+0.98…”
Section: Methodsmentioning
confidence: 99%
“…However, technologies such as LiDAR and TLS can be cost prohibitive [38], and are therefore limited in their application. Recent studies have demonstrated the value of more cost-effective methods of capturing information describing vegetation (fuel) structure and health using image-based point clouds [39,40,41,42,43,44,45]. Image based point clouds are constructed using photogrammetric principles from highly overlapping photography, and the reader is directed to Westoby et al [46] and Snavely et al [47] for further details on the methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recent comparisons of AGB estimations for pasture communities resulted from SfM and TLS techniques (Wallace et al. , Cooper et al. ) showed that both methods allow performing an accurate estimation of the surface biomass.…”
Section: Introductionmentioning
confidence: 99%